Uji Akurasi Hasil Pengukuran GNSS Metode Statik dan RTK-NTRIP dengan Referensi CORS GMU2 - Anandito Hardiyoso; Taftazani, Muhammad Iqbal (Journal of Geospatial Science and Technology, 2025)
Global Navigation Satellite Systems (GNSS) technology continues to develop, including in terms of supporting infrastructure development. One of the latest infrastructure developments is the establishment of the GMU2 Continuous Operating Reference Systems (CORS) station on October 14, 2023, the result of cooperation between DTK Vocational School UGM and PT Kantara Group. This applicative activity aims to test the accuracy of GNSS measurements using static and RTK-NTRIP methods with the CORS GMU2 reference and compare it with CORS JOGS in Yogyakarta. GNSS data was obtained from nine measurement points using static and RTK-NTRIP methods with CORS GMU2 and JOGS as reference stations. The static method refers to the SNI standard Horizontal Control Net with a recording interval of 15 seconds for 20 minutes, while RTK-NTRIP uses real-time correction via the internet. Analysis was conducted through the calculation of standard deviation, RMSE, and significance test of coordinate differences. The results show that the static method with the GMU2 reference produces standard deviations of the Easting component of 0.03 cm to 0.09 cm, Northing of 0.02 cm to 0.09 cm, and height of 0.05 cm to 0.17 cm. The RTK-NTRIP method produces standard deviations of the Easting component of 0.12 cm to 4.46 cm, Northing of 0.11 cm to 5.00 cm, and height of 0.21 cm to 6.77 cm. Although the precision of GMU2 CORS is quite good, its accuracy is lower than that of JOGS CORS, with significant differences at some points. The total RMSE for the static method reached 37.565 cm, while the RTK-NTRIP method ranged from 41.010 cm to 42.572 cm. Significance tests showed significant differences at most points, with null hypothesis rejection of 100% for the static method and 78 to 81% for RTK-NTRIP. In conclusion, further evaluation is needed to ensure the reliability of GMU2 CORS as a reference station.